2016
DOI: 10.1515/pielxxiw-2016-0021
|View full text |Cite
|
Sign up to set email alerts
|

Existential attitudes and Occupational burnout syndrome in nurses

Abstract: Aim. The aim of the study was to determine the relation between existential attitudes and occupational burnout in nurses.Material and methods. The research sample consisted of 120 nurses. Life Attitudes Profile - Revised (the LAP-R) adapted by R. Klamut and Link Burnout Questionnaire (the LBQ) adapted by A. Jaworowska were used in the research.Results. Psycho-physical exhaustion and relationship deterioration correlate negatively with life goals, internal consistency, life control, death acceptance and positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The analysis revealed that psychosocial exhaustion and relationship deterioration coexist indirectly proportionally with life purpose, internal coherence, life control, death acceptance and directly proportionally with existential vacuum and goal seeking. Whereas, the feeling of professional ineffectiveness and disillusion are negatively related to life purpose, internal coherence, life control and are positively related to existential void and goal seeking [17].…”
Section: Discussionmentioning
confidence: 97%
“…The analysis revealed that psychosocial exhaustion and relationship deterioration coexist indirectly proportionally with life purpose, internal coherence, life control, death acceptance and directly proportionally with existential vacuum and goal seeking. Whereas, the feeling of professional ineffectiveness and disillusion are negatively related to life purpose, internal coherence, life control and are positively related to existential void and goal seeking [17].…”
Section: Discussionmentioning
confidence: 97%